Monetary Policy with Foreign Currency Debt - Philippe Bacchetta (Swiss National Bank, Study Center Gerzensee, 2000)
A major feature characterizing recent currency crises in emerging markets has been the large proportion of private foreign currency debt. This feature has made the conduct of monetary policy particularly difficult. This paper proposes a simple model to better understand these issues where firms are credit constrained and the currency denomination of debt matters. I argue that the recent financial crises are well explained by such a model. In this framework, monetary policy can be ineffective since the interest rate and the exchange rate channels of transmission of monetary policy go in opposite directions. This potential ineffectiveness should be taken into account in the choice of a monetary or exchange rate regime.
Keywords: 330; Geldpolitik; Währungskrise; Verbindlichkeiten; Internationale Staatsschulden